Avaliação da vida da ferramenta e mecanismos de desgaste no torneamento convencional e de alto avanço da zona termicamente afetada pelo corte térmico prévio no aço ABNT NBR 6655 grau LN 280 - Barcelos, Maurício Belchor (2022)
Cutting tool life has a significant impact on the final costs of the machined product. Thus, it is essential that criteria be established to define the end of its useful life, in order to mitigate the effects of wear and damage on the geometric quality of the manufactured part and on the machine integrity, and to enhance its use. This need is even more pronounced in the case of machining operations of materials with a high density of geometric irregularities, such as those previously processed by thermal cutting operations, where the rate of tool wear is accelerated. This work comparatively evaluates the tool life and wear mechanisms in conventional and prime turning of ABNT NBR 6655 grade LN280 steel bushings, previously profiled by thermal plasma cutting. Machinability tests were performed using class P carbide tools in trigonal geometries for the conventional tool, and rhombic for the prime turning tool. Both tools consist of a triplex coating based on TiCN+Al2O3+TiN deposited on the flank, and duplex coating based on TiCN+Al2O3+TiN applied on the exit surface. To evaluate the performance of both tools, a standard value of cutting depth was set (1.5 mm) and varied in three levels the cutting speed (140, 160 and 200 m/min) and feed (0.2; 0.3 and 0.4 mm/rev, for conventional; and 0.5; 0.75 and 0.82 mm/rev for prime turning). The end-of-life criterion of the cutting tool was established according to the ISO 3685 standard (VB = 0.6 mm). The performance of the tools was fundamentally evaluated by the comparative analysis between the its wear rates and the finish of the machined part. Wear was determined by measuring the extent of damage on the tool flank using microscopy techniques; while finish was determined by average roughness measurements using a contact surface roughness meter. In order to support the discussion of the machinability test results, the cross sections and surface of the bushings after heat cutting were characterized metallographically using optical microscopy, and by microhardness and residual stress measurements. The results of the preliminary characterization of the bushing show that thermal cutting promotes changes in the microstructure, microhardness and residual stress profile of the cutting edge. The results of the machinability tests reveal that the high feed tool presents better wear performance (longer life). Evaluation of the machined surfaces finish reveals that, isolating the effect of the adopted tool geometry and feed, the average roughness grows at the same rate with the wear of the conventional and high feed tool. The wear mechanisms are the same in conventional and prime turning tools: abrasive on the flank surface, and adhesive on the exit surface. Therefore, the superiority of prime over conventional turning is proven, for the machining conditions evaluated here.